Antibacterial effect of calcium oxide nano-plates fabricated from shrimp shells1. Issue 6 (8th June 2015) - Gedda, Gangaraju; Pandey, Sunil; Lin, Yu-Chih; Wu, Hui-Fen
<x xml:space="preserve">Abstract</x> The formation and characterization of shrimp shell-derived CaO nano-plates with antibacterial activity have been demonstrated in this communication.